Laki-laki memiliki tingkat satiety (fullness) lebih rendah setelah diberikan diet tinggi protein - A Fahmy Arif Tsani; Alifia Evitarani; Fillah Fithra Dieny; Ida Kristiana (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
High-protein food has a significant impact on reducing hunger conditions and increasing satiety. Not many studies have investigated the impact of differences in a high protein diet on satiety based on sex and nutritional status. The aim of the study is to determine the effects of a high protein diet (animal and plant-based) on satiety based on sex and nutritional status. The experimental research was conducted by pre-post group design. The subjects of this research were 23 adults aged 20-23 years who meet the inclusion and exclusion criteria living in Yogyakarta. Satiety profiles (hunger, fullness, desire to eat, and PFC) were measured using a Visual Analogue Scale (VAS) questionnaire. The categorization of nutritional status is based on BMI. Data were analyzed using independent sample t-test and paired t-test. Based on sex, there was a difference in the fullness component between males and females after consuming animal protein meals (p= 0,001) and plant-based protein meals (p< 0,01). Whereas based on nutritional status, there was no difference in all satiety profiles. In conclusion, men have different satiety from women after consuming a high protein diet.